Pemanfaatan Pembangkit Listrik Tenaga Surya Pada Gedung Bertingkat - Tri Joko Pramono; Erlina Erlina; Zainal Arifin; Jef Saragih (KILAT, 2020)
Solar Power Plant is one of the New Renewable Energy power plants. Solar panels can produce unlimited amounts of electrical energy directly taken from the sun, with no rotating parts and no fuel. In this study are optimize solar power plants using hybrid systems with electricity companies and the use of semi-transparent solar panels in high rise buildings to meet the burden of the building. The research will discussed about use of solar power plants using semi-transparent solar panels in multi-storey buildings. The solar panel used for the facade is a semi-transparent solar panel makes its function become two, that is to produce electrical energy as well as glass through which sunlight and can see the view outside the building without reducing the building's aesthetic value. In this study is the value of solar radiation taken from west is the lowest value in November 1.4 Kwh can produce energy PLTS 3,855 Kwh and the highest solar radiation in July amounted to 3.75 Kwh can produce energy PLTS 10.331 Kwh. From the utilization of this PLTS system, Performance Ratio of 85% was obtained using study of 36 panels on the 3rd to 5th floors, this system can be said to feasible.